The c-index is not proper for the evaluation of t-year predicted risks. (16th February 2018) - Blanche, Paul; Kattan, Michael W; Gerds, Thomas A
SUMMARY: We show that the widely used concordance index for time to event outcome is not proper when interest is in predicting a t -year risk of an event, for example 10-year mortality. In the situation with a fixed prediction horizon, the concordance index can be higher for a misspecified model than for a correctly specified model. Impropriety happens because the concordance index assesses the order of the event times and not the order of the event status at the prediction horizon. The time-dependent area under the receiver operating characteristic curve does not have this problem and is proper in this context.